2018
DOI: 10.17116/jnevro201811808185
|View full text |Cite
|
Sign up to set email alerts
|

Circadian changes in the structure of cardiac rhythm during pre-symptomatic and symptomatic stages of Parkinson's disease

Abstract: Многочисленные исследования болезни Паркинсона (БП) свидетельствуют, что неврологические нарушения, возникающие при прогрессирующей дегенерации дофами нергических нейронов нигростриарной системы, не ограничиваются мозгом и часто вызывают тяжелые вегетовисцеральные дисфункции, нарушая в том числе регуляцию сердечно-сосудистой системы (ССС) [1, 2]. Дегенеративные

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…[ 32 ] Markov et al [ 33 ] noticed that heart rate variability showed significant changes in contrasting seasons (winter and summer), with increased parameters of sympathetic activity in winter as compared with summer. In addition, Mamalyga et al [ 34 ] found that abnormal circadian autonomic regulation of the heart only occurred at night in patients experiencing the early symptomatic stages of PD, and in winter nights are the longest as far as we know. Circadian heart-rate variability decreased or even disappeared in patients with advanced PD, suggesting that the ability of autonomic functions to regulate rhythm might be influenced by disease severity.…”
Section: Discussionmentioning
confidence: 99%
“…[ 32 ] Markov et al [ 33 ] noticed that heart rate variability showed significant changes in contrasting seasons (winter and summer), with increased parameters of sympathetic activity in winter as compared with summer. In addition, Mamalyga et al [ 34 ] found that abnormal circadian autonomic regulation of the heart only occurred at night in patients experiencing the early symptomatic stages of PD, and in winter nights are the longest as far as we know. Circadian heart-rate variability decreased or even disappeared in patients with advanced PD, suggesting that the ability of autonomic functions to regulate rhythm might be influenced by disease severity.…”
Section: Discussionmentioning
confidence: 99%